Comparison of Outcome of Intramedullary Interlocking Nail Versus Dynamic Compression Plate for Treatment of Humeral Shaft Fractures - Rizwan Ullah; Khan, Muhammad Imran; Syed, Subhanullah; Ubaid Ullah (Indus Journal of Bioscience Research, 2025)
Background: Humeral shaft fractures are common orthopedic injuries and can lead to significant functional disability if not treated properly. Dynamic compression plate and intramedullary interlocking nail are commonly used surgical techniques for fixation of these fractures, but there is still controversy regarding the better method in terms of functional recovery and outcome. Objective: To compare the frequency of excellent functional outcome with dynamic compression plate and intramedullary interlocking nail for treatment of humeral shaft fractures. Study Design: Randomized controlled trial. Duration and Place of Study: The study was conducted from 16th February 2025 to 16th June 2025 at the Orthopedic A Unit, Khyber Teaching Hospital, Peshawar. Methodology: A total of sixty patients aged between eighteen and sixty years with closed humeral shaft fractures classified under type A1 to A3 of the AO/OTA system were enrolled and randomly divided into two equal groups. Group A underwent open reduction and internal fixation with dynamic compression plate, and Group B received fixation by intramedullary interlocking nail through antegrade or retrograde approach. Patients were followed to evaluate bone healing and functional recovery using the Disabilities of the Arm, Shoulder and Hand scoring system. An excellent outcome was defined as a score below twenty-four. Results: The mean age of participants was 42.48 ± 9.42 years. Excellent functional outcome was achieved in twenty-six patients (86.7%) treated with dynamic compression plate and twelve patients (40.0%) treated with intramedullary interlocking nail, showing a statistically significant difference (p<0.001). Conclusion: Dynamic compression plate fixation provides superior functional outcomes compared with intramedullary interlocking nail for the treatment of humeral shaft fractures.